Magnetic simulations of core–shell ferromagnetic bi-magnetic nanoparticles: The influence of antiferromagnetic interfacial exchange - Ramos-Guivar J.A. (2021)
This research was funded by Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Innovaci?n Tecnol?gica (FONDECYT-CONCYTEC), Project number 177-2020-FONDECYT.